Pengaruh Asimetri Informasi, Profitabilitas dan Ukuran Perusahaan Terhadap Manajemen Laba Pada Perusahaan Sektor Aneka Industri Di Indonesia - Patriandari -; Risti Fitriana (AKRUAL : Jurnal Akuntansi dan Keuangan, 2019)
This study aims to determine the effect of asymmetry of information, profitability and the size of the company to the management company's earnings that occurred in various industry sectors listed on the Indonesia Stock Exchange with the observation period 2011-2013. Purposive sampling method obtained a sample of 24 companies. This study uses the independent variable asymmetry of information, profitability and the size of the company and use the variables that are influenced by the independent variable is management earnings as the dependent variable. Researchers measured the earnings management proxy jones modified the model to determine the value discresionary accruals. Variable asymmetry using the relative bid-ask spread, measured by the ratio Profitability Return on Assets (ROA), while the size of the company uses a proxy log of total assets. Through multiple linear regression analysis known that the asymmetry of information and the size of the company does not effect on earnings management while profitability showed positive effect on earnings management. Simultaneously, the three independent variables shows can jointly affect earnings management significantly with Ftabel of 2.74 is smaller than Fhitung 3.921 with a significance level of 0.012